Peningkatan Hasil Belajar Seni Rupa pada Materi Pencampuran Warna melalui Finger Painting Kelas 1 Sekolah Dasar - Ferry Arif Setiawan Pratama; Akhwani Akhwani; Sianah Sianah (STKIP AL HIKMAH SURABAYA, 2023)
The purpose of this research is to improve fine arts learning outcomes on color mixing material by applying Finger Painting for class IA at SDN Jemur Wonosari 1/417 Surabaya which consists of 28 students, there are 12 boys and 16 girls. The KKM determined by the school is 75. The research method applied is classroom action research (PTK). The instruments used in this research were observation sheets on the researcher's ability to plan learning and the researcher's ability to carry out learning activities, test instruments in the form of multiple choice questions, questionnaires and documentation. The research results show that there is an increase in cognitive learning outcomes in color mixing material. In cycle 1 there were 9 students who had not completed out of 28 with an average score of 67.28. In cycle 2 there was an increase, namely by obtaining an average score of 77.14 and 89.28% of students obtained a score above the KKM. Based on the research results, it can be said that cognitive learning outcomes in color mixing material increase by applying finger painting.